Collective evictions in Brazil: a criticism of the prominent role of the Judicial (Revista ABRA, 2015)
This paper criticizes the so-called “prominent judicial role”, based on the position by the Judicial Branch in cases of collective eviction through judge rulings, in which thousands of people in the poor communities of Brazil are thrown to the streets without further notice.The objective of this research project was to verify acts of cruelty through rulings in cases of collective evictions, where the individual interests of the owners have prevailed over the right to social housing in the big cities of Brazil.Case analysis was the method used from 2012 and 2014 in two situations of great social impact in Brazil. The first situation refers to the restitution of property of the Telemar building in the city of Rio de Janeiro and the second one to the community of Pinheirinho, in São José dos Campos, in the State of São Paulo.